(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Comments on: Further studies of Bolivian crocidolite-Part IV: Fibre width, fibre drift and their relation to mesothelioma induction: Preliminary findings, by Ilgren EB, van Orden DR, Lee RJ, Kamiya YM, Hoskins JA.